Bitumen Modification Using Used Motor Oils to Reduce Short-and Long-term Aging - Kerhali, Okba; Bassam Sultan, (Tishreen University Journal -Engineering Sciences Series,, 2023)
Most of the research and road agencies in the world tend to make the most of the used materials in maintenance or construction operations, as the process of using them constitutes an added value to them as well, in addition to reducing the environmental impact of these materials. In this research, the effect of certain additives (expendable materials) of the bituminous binder on its properties was studied, and the suitability of these additives for use in modifying the asphalt was determined, in order to resist the long-term fatigue that the asphalt binder is exposed to in hot climate conditions, which greatly affects the investment time. Reducing required maintenance. The burnt oil material (resulting from the combustion of oils in internal combustion engines) was chosen for its ease of use and obtaining, in addition to the lack of the need for additional equipment in order to prepare it for use, as it was modified in three weight ratios, and its aging was monitored through a series of laboratory experiments that simulate operations Manufacture and investment of bitumen in asphalt mixtures. The results showed an improvement in the ring & ball temperature and Frass breaking point temperature, and an improvement in the field of thermal plasticity of bitumen after the laboratory aging stages.